Regular 2k-Directional Polygon Algorithm for Finding the Convex Hulls of big data sets in 2D - Kieu Linh, Nguyen; Hoai Thu, Vu (2023 RIVF International Conference on Computing and Communication Technologies (RIVF), 2023)
This paper introduces a regular 2k-directional polygon algorithm for determining the convex hull of n points in: \mathbb{R}^{2} (n can be large). The regular 2k -directional polygon is formed from 2k extreme points in 2k regular directions. The points interior to this polygon can be removed before finding the convex hull. For large k , most of the points of the original set can be discarded. Thus the computation time can be significantly reduced. Specifically, when calculating sequentially, the calculation results show that our algorithm runs faster than the Qhull library, which is the most modern implementation of Quickhull. In parallel computing, our algorithm is efficient when the data is huge, for example with a set of 100 000 000 points, our algorithm can be approximately 12 times faster than Qhull.